The Influence of Students Critical thinking in Learning Christian Religion Education among The Compound Society - Tianggur Medi Napitupulu (Conference Series, 2020)
The purpose of this study was to determine the effect of Critical Thinking of the students at PAK department, IAKN Tarutung, North Sumatra Indonesia. This research hypothesis: "There is a positive and significant influence between students' critical thinking upon Christian religion education (PAK) Subjects in Compounding Communities.The population consisted of 200 students and the sample was taken as 50% of the total population that equals to 100 students. Regression coefficient test showed that r2-obt = 0.6399 and the percentage of influence between the Compounding Society Subjects on the Effectiveness of Critical Thinking is 63.99%. Hypothesis test with simple linear regression variance analysis obtained the value of F-count = 174.22> F¬table (? = 0.05, dk = 30) = 4.00.